2014
DOI: 10.1016/j.physleta.2014.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Thermopower for a molecule with vibrational degrees of freedom

Abstract: We propose a simple model to study resonant tunneling through an organic molecule between to conducting leads, taking into account the vibrational modes of the molecule. We solve the model approximately analytically in the weak coupling limit and give explicit expressions for the thermopower and Seebeck coefficient. The behavior of these two quantities is studied as function of model parameters and temperature. For a certain regime of parameters a rather peculiar variation of the thermopower and Seebeck coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In the instance of plasma combustion, electrons gain energy because of particle collisions into different degrees of freedom via an external electric field. Typical measure of vibrational degrees of freedom is in the range of 1 to 3 K. [50][51][52] This means that for efficient vibrational agitation, the average electron energy should be comparable with or greater than this magnitude (in air it should be in the range of 0.2 to 2 eV). 33,34 This means that the excitation of the internal degrees of freedom is because of the electron energy used up.…”
Section: Plasma Discharge Energy Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the instance of plasma combustion, electrons gain energy because of particle collisions into different degrees of freedom via an external electric field. Typical measure of vibrational degrees of freedom is in the range of 1 to 3 K. [50][51][52] This means that for efficient vibrational agitation, the average electron energy should be comparable with or greater than this magnitude (in air it should be in the range of 0.2 to 2 eV). 33,34 This means that the excitation of the internal degrees of freedom is because of the electron energy used up.…”
Section: Plasma Discharge Energy Branchingmentioning
confidence: 99%
“…For efficient rotational excitation, typical spacing requirement of simple molecules between rotational levels is~10 to 100 K and electron energỹ 300 K (~0.03 eV). Typical measure of vibrational degrees of freedom is in the range of 1 to 3 K. [50][51][52] This means that for efficient vibrational agitation, the average electron energy should be comparable with or greater than this magnitude (in air it should be in the range of 0.2 to 2 eV). Energies of about 3 to 10 eV are required for the dissociation of molecules as well as the excitation of electronical degrees of freedom.…”
Section: Plasma Discharge Energy Branchingmentioning
confidence: 99%
“…4. Moreover, by virtue of the effective adhesion of DNA on a hydrophobic surface of graphene and graphene-like materials due to stacking interaction of their π-electrons, [26][27][28][29] …”
Section: Metal-containing Lb-film Enhancement Of Raman Light Scatterimentioning
confidence: 99%
“…Numerous works are focused on exploring properties of the thermopower of single-molecule junctions. It was shown that the thermopower may be affected by molecular vibrations [11][12][13][14][15][16][17], by effects of molecular bridge geometry [18][19][20][21][22] by interactions between electrons participating in transport [23][24][25][26][27][28][29][30] and by photons [31]. Under certain conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%